Mortality and crown conditions on Quercus robur L. permanent plots - a 20-year overview - Matjaž Čater (Slovenian Forestry Institute, 2014)
Pedunculate oak (Quercus robur L.) forests in Slovenia are experiencing widespread mortality. Changes in lowlands are reflected in decline of complete forest complexes, high mortality, uneven stand structure and associated forest regeneration problems. Prediction of the present-tree response in disturbed forest ecosystems may significantly contribute to better guideline policies for the silvicultural and forest management practice in the changing environment in both stressed and stabile forest ecosystems. Data from annual crown condition surveys in the 1995-2014 period from four permanent plots have been compared with parameters from hemispherical photo analysis and hydrometeorological data. Good agreement has been confirmed between crown defoliation and total openness; all parameters from the hemispherical photo analysis, which were corrected for winter period values, also indicated a better agreement. Mortality rate and crown defoliation correlated well with extreme drought events. Pattern of agreement among compared parameters was different for the Krakovski gozd and Dobrava plots on one hand and Cigonca and Hraščica plots on the other hand. Mortality is influenced by the average air temperatures much more than by precipitation and groundwater table oscillations